The Universality and Variation of Flower Metaphors for Love in English and Chinese Poems - et. al., Didi Li, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Metaphor is ubiquitous in everyday life, not only in language but also in action and thought (Lakoff & Johnson, 1980). Difficult, intangible and abstract concept can be understood by applying metaphor. Emotion is viewed as a kind of abstract and private personal experience. Many of the metaphors have been studied by cognitive linguists over the past two decades, emotional metaphor is an important aspect of cognitive linguistics, and love has become one of the focuses of the researches. By applying the conceptual metaphor theory as a framework, this paper focuses on analyzing flower metaphors for love from the cross-cultural perspective based on figurative expressions in Chinese and English poems. The results of the study suggest that flower metaphors for love are likely to be near-universal at a general level in English and Chinese poems because of universal experiences, while cross-cultural variations and diversity exist in English and Chinese poems in culture-specific ways at a specific level in virtue of cognitive preferences.